Determination of Optimum Velocity for Various Nanofluids Flowing in a Double-Pipe Heat Exchanger - Dalkilic, Ahmet Selim; Acikgoz, Ozgen; Gumus, Muhammed Ali; Wongwises, Somchai (TAYLOR & FRANCIS INC, 2017)
Piping is one of the most important issues in the cost of process factories. It is known that 80% of bought equipment cost or 20% of overhead capital can belong to piping cost in a fluid-process factory. Pipe diameter and therefore flow velocity strongly affect the existing value of the factory regarding the consumed electric energy and fitting cost of pipes, pumps, and valves. We give a detailed cost analysis model for the pure fluids of water, motor oil, glycerin, ammonia, methanol, ethanol, ethylene glycol, and propane and their nanofluid mixtures with Ti and TiO2 particles in liquid phase flowing in the tube side of a double-pipe heat exchanger. Pressure drop and pumping power values increase with flow velocity but total cost values show an arc with it. The clear outcome is that there is a minimum cost value as a result of the analyses for each investigated fluids. Moreover, validation of the model is performed by plotting the calculated items in figures such as total heat transfer coefficient versus Reynolds number, pressure drop versus Reynolds number, and friction factor versus mass flow rate. Characteristics of the trend lines in these figures are seen as they should be.
Keywords: THERMAL-CONDUCTIVITY; THERMOPHYSICAL PROPERTIES; AL2O3-WATER NANOFLUIDS; PRESSURE-DROP; LAMINAR-FLOW; FLUID-FLOW; ENHANCEMENT; Thermodynamics; Engineering; Mechanics